'A disoriented vision of … fact': Brian Friel, Francis Bacon, and Faith Healer. Issue 2 (November 2020) - Kuczyńska, Zosia
Abstract : The Brian Friel Papers at the NLI reveal a long and relatively unexplored history of major and minor influences on Friel's plays. As the archive attests, these influences manifest themselves in ways that range from the superficial to the deeply structural. In this article, I draw on original archival research into the composition process of Friel's genre-defining play Faith Healer (1979) to bring to light a model of influence that operates at the level of artistic practice. Specifically, I examine the extent to which Friel's officially unacknowledged encounter with a book of interviews with painter Francis Bacon influenced the play in terms of character, language, and form. I suggest that Bacon's creative process – incorporating his ideas on the role of the artist, the workings of chance, and the extent to which art does violence to fact – may have had a major influence on both the play's development and on Friel's development as an artist.